Linearity assessment according to IUPAC guidelines for the determination of plasticizers in plasters food packaging by gas chromatography - Sanagi, Mohd. Marsin (2008)
Linearity assessment as a required performance in method validation has always been subject to different interpretations and definitions by various guidelines and protocols. However, there are very limited applicable implementation procedures that can be followed by laboratory chemist in assessing linearity. Thus, this work proposes a simple method for linearity assessment in method validation by a regression analysis that covers experimental design, estimation of the parameters, outlier treatment, and evaluation of the assumptions according to IUPAC Guidelines. The suitability of this procedure was demonstrated by its application to an in-house validation for the determination of plasticizers in plastic food packaging by gas chromatography.